1995
DOI: 10.1002/ppul.1950190103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pseudomonas aeruginosa colonization on lung function and anthropometric variables in children with cystic fibrosis

Abstract: The aim of this study was to evaluate how lung function and growth changed over time in children with cystic fibrosis (CF) colonized with pseudomonas aeruginosa (Pa) compared with those free of the organism. A total of 192 children attended our cystic fibrosis clinic between 1982 and 1992. Sixty-two of these had three or more annual assessments for lung function, and 117 had three or more annual assessments for height and weight. When lung function was expressed as a standard deviation score (SDS), forced expi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 20 publications
3
83
0
2
Order By: Relevance
“…Subsequently, Kerem et al 18 found that at 7 years of age, CF patients colonized with P aeruginosa had a significantly lower forced expiratory volume in 1 second compared with uninfected patients. Other data 19,20 also indicate a relationship between pulmonary dysfunction and pseudomonas-positive cultures. In addition, recent observations by McCubbin et al 21 have identified an association between pseudomonas infections and the development of bronchiectasis in young children with CF.…”
Section: Lished Wilmott Et Almentioning
confidence: 99%
“…Subsequently, Kerem et al 18 found that at 7 years of age, CF patients colonized with P aeruginosa had a significantly lower forced expiratory volume in 1 second compared with uninfected patients. Other data 19,20 also indicate a relationship between pulmonary dysfunction and pseudomonas-positive cultures. In addition, recent observations by McCubbin et al 21 have identified an association between pseudomonas infections and the development of bronchiectasis in young children with CF.…”
Section: Lished Wilmott Et Almentioning
confidence: 99%
“…The association between P. aeruginosa infection and measures of CF disease severity is clearly established, including increased rate of lung function decline, greater need for antibiotics and hospitalization, and decreased survival (2)(3)(4)(5)(6)(7)(8)(9)(10). Although there is a parallel between declining health and the progression from early to chronic P. aeruginosa, gaps remain in understanding the changes that P. aeruginosa undergoes during this critical transition period (11).…”
mentioning
confidence: 99%
“…Chronic PA colonisation is associated with a lower FEV 1 in childhood , an accelerated rate of FEV 1 decline (Pamukcu et al, 1995;Kosorok et al, 2001;Emerson et al, 2002), a shorter median life expectancy (CFF Registry, 1996;Emerson et al, 2002) and much higher treatment costs (Baumann et al, 2003). Preventing this colonisation is considered the most important challenge for the CF clinician, as it frequently determines the patient's future quality of life and long-term survival (CF Trust 2002;Koch, 2002).…”
Section: Challenge 1: Postpone Chronic Colonisation By Pseudomonas Aementioning
confidence: 99%